Association of Body Dysmorphic Disorder with Leptin Levels in Patients with Normal Weight Undergoing Liposuction: A Matched Case Study - Chatchai Pruksapong, MD, FRCST; Supat Chamnanchanunt, MD; Vipa Thanachartwet, MD; Varunee Desakorn, MPH, MSc; Daochompu Nakawiro, MD; Duangjai Sahassananda, MSc; Ponlapat Rojnuckarin, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2019)
Background:. Liposuction is the most common aesthetic surgical procedure performed globally. Some of the patients with normal weight who seek liposuction may suffer from body dysmorphic disorder (BDD). Leptin, which is mainly produced by adipose tissue, may be associated with this condition. The aim of this study was to determine the prevalence of BDD and leptin levels in patients with normal weight seeking liposuction.